Molecular docking of 8'-halogen substituted spiro derivatives of tetrazolo[1,5-c]quinazoline to 11-betahydroxysteroid dehydrogenase 1 - Antypenko, O.; Mesdud, S.; Brytanova, T.; Antypenko, L.; Британова, Тетяна Сергіївна; Антипенко, Олексій Миколайович (My University, 2024)
The aim of the work. To elucidate the binding affinity and molecular interactions of potential ligands with 11β-HSD1, we employed molecular docking as a computational approach. This in silico technique is used for exploration of conformational space and the identification of compounds exhibiting high binding affinity for this specific enzymatic target, thereby enhancing the predictive power of structure-based drug design strategy.
Keywords: тези доповідей